Effect of Flipped Classroom on the Grammatical Competence of Grade 7 Learners - Llabore, Joven S. (Alipato, A Journal of Basic Education; Vol 15 (2024): Alipato, A Journal of Basic Education, 2025)
Flipped classroom is a student-centered, collaborative-driven language teaching strategy that aims to improve the content knowledge of the learners. Given the challenges students face in mastering grammar, this study explored how this approach could support their learning. This study employed pretest-posttest research design to determine the effect of flipped classroom on the grammatical competence of Grade 7 learners. Since the success of flipped classroom relied on well-prepared instructional materials, the researcher designed four weekly plans and prepared four video presentations in English grammar (active and passive voices of the verb, present and past tenses of the verb, subject-verb agreement, and pronoun-antecedent agreement). The participants from the experimental group and control group underwent pretest and posttest. The result of the pretest and posttest of the participants was analyzed and compared using mean, standard deviation, Mann-Whitney U test, and Wilcoxon Signed Rank Test. The result showed that there is an increase in the scores of the posttest of both groups and that there was no significant difference between the posttest achievements of students in the traditional method and the flipped classroom. However, in light of the challenges faced by traditional teaching method, flipped classroom can be a viable alternative for schools.